Too late for indigenous climate justice: Ecological and relational tipping points. (23rd October 2019) - Whyte, Kyle
Abstract: It may be too late to achieve environmental justice for some indigenous peoples, and other groups, in terms of avoiding dangerous climate change. People in the indigenous climate justice movement agree resolutely on the urgency of action to stop dangerous climate change. However, the qualities of relationships connecting indigenous peoples with other societies' governments, nongovernmental organizations, and corporations are not conducive to coordinated action that would avoid further injustice against indigenous peoples in the process of responding to climate change. The required qualities include, among others, consent, trust, accountability, and reciprocity. Indigenous traditions of climate change view the very topic of climate change as connected to these qualities, which are sometimes referred to as kin relationships. The entwinement of colonialism, capitalism, and industrialization failed to affirm or establish these qualities or kinship relationships across societies. While qualities like consent or reciprocity may be critical for taking coordinated action urgently and justly, they require a long time to establish or repair. A relational tipping point, in a certain respect, has already been crossed, before the ecological tipping point. The time it takes to address the passage of this relational tipping point may be too slow to generate the coordinated action to halt certain dangers related to climate change. While no possibilities for better futures should be left unconsidered, it's critical to center environmental justice in any analysis of whether it's too late to stop dangerous climate change. This article is categorized under: Climate, Nature, and Ethics > Climate Change and Global Justice Abstract : Treaties and kinship bonds in the Great Lakes region in North America ‐ historically and today ‐ are ways in which indigenous peoples seek to engender relational qualities of reciprocity, trust, consent, and accountability connecting humans and nonhumans. U.S. and Canadian violations of these qualities lessen environmental resilience and increase risks to indigenous peoples from climate change impacts and mitigation projects.